Secure Intrusion Detection System in Mobile Ad Hoc Networks Using RSA Algorithm - Sankaranarayanan, S.; Murugaboopathi, G. (2017 Second International Conference on Recent Trends and Challenges in Computational Models (ICRTCCM), 2017)
Nowadays Mobile Ad Hoc Networks has become a popular research subject due to its characteristics. Generally Mobile Ad Hoc Networks have given the low physical security for mobile devices. With this problem there are many chances that the intruders may attack the nodes over the function. Using Intrusion Detection Techniques we can find the intruders before it may attack the nodes. Intrusion Detection System (IDS) is considered as the first line of defence for security in MANET. In this paper we discuss intrusion detection system using public RSA algorithm.